Hegemonic Masculinity in The Super Mario Bros (2023) - Anggi Khairizah Harahap; Morada Tetty (International Journal of Educational Development, 2025)
This study explores the representation of hegemonic masculinity in The Super Mario Bros (2023), focusing on the character Bowser as a central figure of dominance and authority. Using Connell’s (2005) theory of hegemonic masculinity, this research identifies the masculine traits manifested through Bowser’s verbal and non-verbal expressions. The study employed a qualitative descriptive method with textual analysis on thirty selected scenes from the film. The findings reveal that Bowser exhibits all seven traits of hegemonic masculinity, including aggression and competition, dominance and control, physical strength, emotional restraint, risk-taking, sexual conquest, and self-confidence. Among these, aggression and competition (23.3%) and dominance and control (20%) are the most prominent. Bowser’s masculinity reflects how patriarchal ideals are embedded within modern animated cinema, emphasizing control, strength, and emotional suppression. This study contributes to the understanding of how traditional masculinity continues to be reproduced in contemporary media, influencing audience perceptions of male identity and power.